Ethylene and carbon dioxide production of starfruits (Averrhoa carambola L.) stored at various temperatures and in different gas and relative humidity atmospheres - Lam, P. F.; Wan, C. K. (West Indian Agricultural College, 1987)
The respiration pattern of starfruits stored at 5°Cremained rather uniform with little change being observed as indicated by the amount of carbon dioxide evolved. No ethylene was detected at this temperature. The respiration rates of fruits stored in atmospheres without ethylene and the control showed a decreasing trend, and this was similarly shown by fruits stored in low and high relative humidity atmospheres. There was no autocatalytic production of ethylene when the fruits were treated with ethylene.